Gerontological nursing in Malaysia: issues and challenges - Syed Elias, Sharifah Munirah (2018)
In recent years, Malaysia’s older population has been increasing. According to census data, the entire population increased from 18.4 million people in 1990 to 28.3 million in 2010 and 31.7 million in 2016. The population is expected to be approximately 33.3 million in 2020 which is an increment of 80% over the three decades. Moreover, the population of older people is expected to increase from 1.05 million to 3.26 million within the same duration — an increment of 210%. Although the Malaysian population reported an increased trend of older people, the numbers of registered nurses with certification in gerontological nursing is low. Several factors were found to be associated to this issue such as; (1) Gerontological nursing is not a desirable career preference; (2) Stigma in caring for older people (3) Lack of skills and knowledge in gerontological nursing and (4) Negative societal perceptions on older people. To address these issues, gerontological nursing needs to be firmly embedded in undergraduate and postgraduate curricula to enable Malaysia’s current and future generations of nurses to develop skills to assess and manage the older people. Further, a mechanism should exist to overcome the negative perceptions of older people in society